Application of simple additive weighting in the decision support system for determining the best location of temporary waste storage places - Isminarti Isminarti; Deny Wiria Nugraha; Yuri Yudhaswana Joefrie; Andipa Batara Putra; Widya Wisanty (International Journal of Artificial Intelligence Research, 2023)
Waste is a material that is discarded or discarded as a result of human or natural activities. The increase in waste is proportional to the level of human use of goods used in everyday life. Until now, the waste problem has always been a complaint for all people in cities and villages. One effective way to deal with the waste problem is to select the ideal location for a Temporary Waste Storage Site (TPS). This research aims to build a system that can determine the best location for waste TPS using a Decision Support System (DSS) method of Simple Additive Weighting (SAW). In this study, seven assessment criteria were used with 148 test data. The tests showed that the computing time required to get the ranking was 12,528 seconds, and memory usage was 226,2422 kb. Also, this system produces an accuracy level of 93.24%, which shows that it can function well using the SAW method and has a pretty good level of accuracy.Â Â Â